The Impact of Electronic Reading Devices on Reading Speed and Comfort in Patients with Decreased Vision - Henry L. Feng; Daniel B. Roth; Howard F. Fine; Jonathan L. Prenner; Kunjal K. Modi; William J. Feuer (Journal of Ophthalmology)
Background/Aims. To evaluate the impact of back-illuminated and nonilluminated electronic reading devices on reading speed and comfort in patients with decreased vision. Methods. A prospective study involving a convenience sample of 167 patients at a single retina practice from January 2011 to December 2012. Participants were asked to read five different excerpts on five different media in a randomly assigned order. Media included a printed book at 12-point font (12PF), iPad2 at 12PF, iPad2 at 18-point font (18PF), Kindle2 at 12PF, and Kindle2 at 18PF. Reading speed in words per minute (WPM) and medium preference were recorded and stratified by visual acuity (VA). Results. Mean reading speeds in WPM: iPad2 at 18PF (217.0), iPad2 at 12PF (209.1), Kindle2 at 18PF (183.3), Kindle2 at 12PF (177.7), and printed book at 12PF (176.8). Reading speed was faster on back-illuminated media compared to nonilluminated media. Text magnification minimized losses in reading performance with worsening patient VA. The majority of participants preferred reading on the iPad2 at 18PF. Conclusions. Back-illuminated devices may increase reading speed and comfort relative to nonilluminated devices and printed text, particularly in patients with decreased VA.